Electron system correlated by the zero-point field: physical explanation for the spin-statistics connection. (March 2016) - Cetto, A M; de la Peña, L
Abstract: Which is the physical agent behind the antisymmetry of the electron state vectors? With the purpose to find an answer to this key question, we analyze the stationary states of a system containing two noninteracting electrons, using the tools of stochastic electrodynamics. In previous work, the resonant response of two particles to common modes of the random zero- point field has been shown to lead to the nonfactorizability of the composite state vector. Here we extend the analysis to particles with spin. When two electrons constitute a single system, a correlation is established between their dynamical variables through the common relevant modes of the zero-point field, which acts as a mediator. An analysis of the exchange properties of the bipartite state vectors obtained is shown to lead to the connection between spin and symmetry. The conclusion is that due consideration of the vacuum field in first quantization leads to the corresponding statistics for an assembly of electrons.